Cultural Characteristic of Early Christianity - Petrosyan, Nelli (Տիգրան Մեծ)
The article presents the cultural characteristic of early Christianity in Armenia. In the end of the 3rd century Christianity had a large number of followers. Christianity gave an opportunity to resist with national unity the external invaders and protect national independence and autonomy. As-sessing correctly the situation, in 301 Tiridates III (287-330) by the initiative of Gregory the Illumi-nator declared Christianity as a state religion in Armenia. Gregory the Illuminatore could show that only due to Christianity it was possible to ensure the further history of Armenian people. He also explained the philosophical-anthropological bases of that religion, contrasting that with the visible simplicity of polytheism.
Keywords: Armenian alphabet; Christianity